Pengaruh Perbandingan Terigu dan Tepung Sukun (Artocarpus communis) Terhadap Sifat Kimia dan Sensoris Kue Nastar - Prayugo, Pandu; Kencana Putra, I Nengah; Suparthana, I Putu (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 11 No 4 (2022): Jurnal ITEPA, 2022)
This study were conducted to determine the effect of wheat flour and breadfruit flour ratio on the chemical and sensory properties of nastar cakes and to obtain the right wheat flour and breadfruit flour ratio to produce nastar cakes with the best characteristics. The experiment was designed with a completely randomized design (CRD). The treatment was the ratio of wheat flour and breadfruit flour (100%: 0%, 90%: 10%, 80%: 20%, 70%: 30%, and 60%: 40%) which was repeated 3 times to produce 15 experimental units.  The data obtained were analyzed by the analysis of variance and if the treatment had a significant effect, then it was continued with the Duncan Multiple Range Test.  The results showed that the ratio of wheat flour and breadfruit flour had a significant effect on the ash, protein, fat, carbohydrate, and crude fiber content, and also on the hedonic test result of color, taste, aroma and overall acceptance.  Base on the chemical and sensory properties, the optimum ratio of wheat flour and breadfruit flour in the making of nastar cakes was 90%: 10%.   The nastar cakes produced had water, ash, protein, fat, carbohydrate, and crude fiber content of 2.28%, 1.18%, 5.76%, 25.44%, 65.32%, and 3.54% respectively.  The sensory properties of the nastar cakes include the liking color, flavor, aroma, and overall acceptance, as well as the crispy texture.